PENGARUH CITRA MEREK, KUALITAS PRODUK DAN DAYA TARIK IKLAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK MIE INSTAN MEREK SEDAAP DI KOTA DENPASAR - Ni Kadek Ria Dwi Wandasari; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2020)
Purchasing decision is an action taken by consumers that leads to the act of purchasing products with the intention of these actions to meet their needs. Brand image becomes one of the factors in influencing purchasing decisions, consumers tend to trust more products with well-known brands that are already widely on the market, consumers will also buy a product with good quality, if the quality of the product is not good consumers will be reluctant to buy it. The attractiveness of advertising also plays an important role in purchasing decisions. Advertising through television is the most attractive ad compared to advertising through other media. attractive advertisements reinforce the interest and desire to buy. Mie Sedaap uses famous people as endosers to attract the attention of consumers. This study is to determine the effect of brand quality product image and attractiveness of advertisements on purchasing decisions. The sample in this study were 100 respondents in the city of Denpasar. Determination of the sample using purposive sampling. The analysis used is multiple linear regression analysis. The results showed that the Brand Image variable had a positive effect on the Consumer Purchase Decision variable with a significant value of (0.001 <0.05). The results showed that the variable Product Quality had a positive effect on Purchasing Decisions with a significant value of (0.020 <0.05). The results showed that the Attractiveness Ad variable had a positive effect on Purchasing Decisions with a significant value of (0,000 <0.05).